FRET-based reporter assesses lysosomal DNA-degradation ability in live cells - Jared Morse; Ka Ho Leung (Sensors and Actuators Reports)
Lysosomes are multifunctional organelles that serve as the cell's central hub for metabolic signaling. Lysosomal malfunction disrupts intracellular homeostasis, leading to adverse health effects. Therefore, assessing lysosomal function is vital for advancing disease understanding and guiding therapeutic development. The existing evaluation methods rely primarily on monitoring lysosomal pH and protein degradation. Here we introduce a DNA-based reporter to evaluate lysosomal activity by assessing the DNA-degradation ability of lysosomes using fluorescence imaging. We successfully monitored the lysosomal DNA-degradation ability in dysregulated lysosomes and lysosomes in drug-induced disease model of NP-A/B and NP-C. We found that both pharmacologically induced models resulted in significant reduction in lysosomal DNA-degradation ability. This tool for monitoring lysosomal activity offers valuable insights for both therapeutic development and understanding disease progression.